Educational Intervention Program for Young Voters: Improving Political Knowledge and Voting Behavior in the 2020 Simultaneous Local Elections - Shadiqi, Muhammad Abdan; Ernawati, Gusti; Hariati, Rima; Arasy, Khaerullah Fadhli Hasan; I’anah, Noor; Al Istiqomah, Wita; Firman, Ulfiyah Nanda; Erlyani, Neka (Jurnal Politik, 2022)
Young voters' low level of political knowledge, which impacts political participation, is still a phenomenon today. The influence of political knowledge on young voters' behavior is still being debated, and there is little empirical evidence, especially regarding political knowledge and voting behavior enhanced through specific educational programs. Therefore, an effective education program is needed to increase political knowledge and the desire of young voters to participate in general elections. This study aims to determine the effectiveness of educational programs in increasing political knowledge and shaping voting behavior among young voters in South Kalimantan Local Elections (Pilkada). We used a quasi-experimental research design by providing extension activities as an online educational intervention program to 41 participants. All participants took three measurement phases, starting from the pre-education program, post-education program, and post-Pilkada phase. The education program was conducted online by providing materials related to the reasons for using the right to vote, information on candidates, considerations for making choices, election techniques, and time and place for the election. The results of the analysis found that educational programs influenced the political knowledge and voting behavior of young voters. Thus, this educational program can significantly and effectively improve young voters' political knowledge and voting behavior.